Characterization of Activity of a Potential Food-Grade Leucine Aminopeptidase from Kiwifruit. (10th October 2010) - Premarathne, A. A. A.; Leung, David W. M.
Abstract : Aminopeptidase (AP) activity in ripe but firm fruit of Actinidia deliciosa was characterized using L-leucine-p-nitroanilide as a substrate. The enzyme activity was the highest under alkaline conditions and was thermolabile. EDTA, 1, 10-phenanthroline, iodoacetamide, andZn 2 + had inhibitory effect while a low concentration of dithiothreitol (DTT) had stimulatory effect on kiwifruit AP activity. However, DTT was not essential for the enzyme activity. The results obtained indicated that the kiwifruit AP was a thiol-dependent metalloprotease. Its activity was the highest in the seeds, followed by the core and pericarp tissues of the fruit. The elution profile of the AP activity from a DEAE-cellulose column suggested that there were at least two AP isozymes in kiwifruit: one unadsorbed and one adsorbed fractions. It is concluded that useful food-grade aminopeptidases from kiwifruit could be revealed using more specific substrates.